Haloperidol induces pharmacoepigenetic response by modulating miRNA expression, global DNA methylation and expression profiles of methylation maintenance genes and genes involved in neurotransmission in neuronal cells - Swathy, Babu; Banerjee, Moinak (PLOS ONE, 2017)
Introduction Haloperidol has been extensively used in various psychiatric conditions. It has also been reported to induce severe side effects. We aimed to evaluate whether haloperidol can influence host methylome, and if so what are the possible mechanisms for it in neuronal cells. Impact on host methylome and miRNAs can have wide spread alterations in gene expression, which might possibly help in understanding how haloperidol may impact treatment response or induce side effects. Methods SK-N-SH, a neuroblasoma cell line was treated with haloperidol at 10μm concentration for 24 hours and global DNA methylation was evaluated. Methylation at global level is maintained by methylation maintenance machinery and certain miRNAs. Therefore, the expression of methylation maintenance genes and their putative miRNA expression profiles were assessed. These global methylation alterations could result in gene expression changes. Therefore genes expressions for neurotransmitter receptors, regulators, ion channels and transporters were determined. Subsequently, we were also keen to identify a strong candidate miRNA based on biological and in-silico approach which can reflect on the pharmacoepigenetic trait of haloperidol and can also target the altered neuroscience panel of genes used in the study. Results Haloperidol induced increase in global DNA methylation which was found to be associated with corresponding increase in expression of various epigenetic modifiers that include DNMT1, DNMT3A, DNMT3B and MBD2. The expression of miR-29b that is known to putatively regulate the global methylation by modulating the expression of epigenetic modifiers was observed to be down regulated by haloperidol. In addition to miR-29b, miR-22 was also found to be downregulated by haloperidol treatment. Both these miRNA are known to putatively target several genes associated with various epigenetic modifiers, pharmacogenes and neurotransmission. Interestingly some of these putative target genes involved in neurotransmission were observed to be upregulated while CHRM2 gene expression was down regulated. Conclusions Haloperidol can influence methylation traits thereby inducing a pharmacoepigenomic response, which seems to be regulated by DNMTs and their putative miRNA expression. Increased methylation seems to influence CHRM2 gene expression while microRNA could influence neurotransmission, pharmacogene expression and methylation events. Altered expression of various therapeutically relevant genes and miRNA expression, could account for their role in therapeutic response or side effects.